Experimental Investigation on the Effect of Container Geometry Change to Liquid Sloshing - Putra, Azma (Trans Tech Publications, 2012)
Liquid sloshing is any motion of free liquid surface inside its container. Sloshing may generate hydrodynamics loads that can be dangerous to structural integrity and stability of moving container. In this study, liquid sloshing in cubical and cylindrical containers with similar characteristic length were investigated. The containers with liquid inside were excited sinusoidally by using an electrodynamics shaker while the free liquid surface level change was captured by using high speed camera. The highest free liquid surface level difference obtained for cylindrical and cubical containers were compared. Results show that cylindrical containers produce less liquid sloshing and thus more suitable to be used for liquid transportation.